Effect of constant light and immobilization stress on rat submandibular saliva secretory response induced by cholinergic and peptidergic agonists - Raquel Gallará; Rubén Ponce; Viviana Centeno; Salvador Bellavía (Universidad de Concepción., 2018)
The aim of this work was to analyse the parasympathetic control of submandibular saliva secretory response to cholinergic and peptidergic agonists in rats chronically exposed to constant light or repeated immobilization. Thirty two adult male Wistar rats were used: LL (8 rats exposed to constant light for 20 days), IMO (8 rats submitted to 14:10 h light: dark cycle and immobilized 2 hours daily for 7 days), and control (16 rats not exposed to stress and submitted to 14:10 hours light:dark cycle). Saliva was collected under anesthesia from the salivary ducts of submandibular glands under increasing doses of methacholine and substance P. Secretory responses (μg/saliva/mg dry weight gland) to methacholine were significantly higher in LL and IMO groups compared to control for the following doses (μg/kg body weight): 3 (153±9 versus 46±3, p<0.001 and 76±3 versus 40±3, p<0.001), 10 (379±23 versus 277±8, p<0.001 and 275±19 versus 250±10, p<0.01) and 30 (729±25 versus 695±19, p<0.05 and 1008±39 versus 640±20, p<0.001). Also, responses to substance P were significantly increased in LL and IMO groups compared to control for the following doses: 0.2 (80±3 versus 30±3, p<0.01 and 94±16 versus 31±3, p<0.001), 0.5 (328±20 versus 231±16, p<0.01 and 531±31 versus 219±25,p<0.001), 1 (681±35 versus 547±30, p<0.01 and 1031±63 versus 563±53, p<0.001), and 5 (2222±88 versus 1868±59, p<0.01 and 3230±145 versus 1921±218, p<0.001). In conclusion, supersensitivity of secretory response to both agonists suggests that chronic exposure of rats to stressors capable of activating the sympathetic adrenal system promotes inhibition of the parasympathetic control of salivary secretion